A blended psychosocial support program for partners of patients with amyotrophic lateral sclerosis and progressive muscular atrophy: protocol of a randomized controlled trial - Jessica de Wit; Anita Beelen; Constance H. C. Drossaert; Ruud Kolijn; Leonard H. van den Berg; Johanna M. A. Visser-Meily; Carin D. Schröder (BMC Psychology, 2018)
Abstract Background Informal caregivers of patients with Amyotrophic Lateral Sclerosis (ALS) or Progressive Muscular Atrophy (PMA) face stressful demands due to severe impairments and prospect of early death of the patients they care for. Caregivers often experience feelings of psychological distress and caregiver burden, but supportive interventions are lacking. The objective of this study is to investigate the effectiveness of a psychosocial support program aimed at enhancing feelings of control over caregiving tasks and reducing psychological distress. This support program is based on an existing program for adult partners of people with cancer and is adapted to meet the needs of ALS caregivers. Methods This study is a randomized controlled trial using a wait-list control design. One hundred and forty caregiver-patient dyads, recruited from a nationwide database and through the website of the Dutch ALS Center, will be either randomized to a support program or a wait-list control group. The blended intervention is based on Acceptance and Commitment Therapy and consists of 1 face-to-face contact, 6 online guided modules and 1 telephone contact. The intervention can be worked through in 8 weeks. The effectiveness and the participants’ satisfaction with the intervention will be evaluated using a mixed method design. Caregivers and patients will be asked to fill in questionnaires on 4 occasions during the study: baseline, 3 months, 6 months and 9 months. The main study outcome is the psychological distress of the caregiver assessed with the Hospital Anxiety and Depression Scale. Secondary outcomes are caregiver burden, caregiver quality of life, quality of life of the patient and psychological distress of the patient. Group differences in primary and secondary outcomes at 6 months will be compared with linear mixed model analysis. In a subgroup of caregivers we will explore experiences with the support program through semi-structured interviews. Usage of the online modules will be logged. Discussion The study will provide insights into the effectiveness of a blended psychosocial support program on psychological distress of caregivers of patients with ALS or PMA, as well as into indirect relations with patients’ wellbeing. Trial registration Netherlands Trial Registry NTR5734, registered 28 March 2016.